Acculturative game design with Latine communities: a bridging review on acculturative stress, behavior change, and serious games - Conde, Samantha; Elor, Aviv; Mateas, Michael; Kurniawan, Sri (Frontiers in Education, 2023)
Acculturative stress disproportionately impacts first-generation Latine-Americans, leading to significant mental health risks stemming from intergenerational cultural norms around gender identity and sexuality. Facilitating communication is critical in reducing this stress, yet it can be challenging for Latine individuals to take the first step in expanding their views due to limited resources, cultural pressure, and motivational needs. On the other hand, serious games provide a unique opportunity to address this challenge by introducing novel experiences to encourage the growth of perspectives in acculturative norms. This article presents a narrative review that bridges three key concepts: (1) acculturative stress in Latine-American communities, (2) modern behavior change theory and model, and (3) the design of serious games. We conclude by proposing a framework for Acculturative Game Design (AGD) and discuss considerations for fostering the support of intergenerational relationships around Latine identity.